Abelhas Nativas Brasileiras: Digital Game as a Tool to Support Environmental Education for Children and Youth - Oda, Álvaro K. de Souza; Braga, Nicole de O.; Lisboa, Luciane C. de Oliveira; Sousa, Pedro M. de (Anais do Workshop de Sistemas de Informação (WSIS); 2024: Anais do XV Workshop de Sistemas de InformaçãoDO - 10.5753/wsis.2024.33693, 2024)
This article presents the development, application and evaluation of an educational game developed on the Unity platform called “Abelhas Nativas Brasileiras”. It was developed to help students develop environmental education and proposes scenarios where the player takes control of native Brazilian bees, facing the main causes of the decline in the population of these species in the form of villains. The game was evaluated using a usability test, applied in 2 schools to children aged between 7 and 12. With a focus on raising awareness, the game promises to be a dynamic approach to helping build knowledge, socio-environmental values and the protection of the natural environment.